2022
DOI: 10.1057/s41262-022-00275-9
|View full text |Cite
|
Sign up to set email alerts
|

Organizational resilience and internal branding: investigating the effects triggered by self-service technology

Abstract: The majority of studies on internal brand equity examine its various dimensions and relationships between them. While prior research specifies organizational practices relevant for successful internal branding, the insights about the impact of essential organizational factors on internal brand equity are still limited. This study focuses on organizational resilience that is vital for the existence of organizations not only during a crisis, but also during everyday operations. The main purpose of this study is … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 98 publications
(145 reference statements)
0
7
0
Order By: Relevance
“…The theoretical and methodological principles of brand creation and management have been covered by the following scientists in their works: D. Akker (Moore, 2016), T. Ambler, L. Balabanova, J. Bernett, G. Biedenbach (Biedenbach, 2022), O. Bilan, T. Grigorchuk, G. Calach (Kalach, 2020), K. Keller (Keller, 2020), B. Cova (Cova, 2022, S. Kovalchuk (Kovalchuk, 2021), P. Kotler (Kotler, 2016), Y. Larina, Y. Marchuk, O. Zozulov, V. Parcak, Vol. 9 No.…”
Section: Research and Resultsmentioning
confidence: 99%
“…The theoretical and methodological principles of brand creation and management have been covered by the following scientists in their works: D. Akker (Moore, 2016), T. Ambler, L. Balabanova, J. Bernett, G. Biedenbach (Biedenbach, 2022), O. Bilan, T. Grigorchuk, G. Calach (Kalach, 2020), K. Keller (Keller, 2020), B. Cova (Cova, 2022, S. Kovalchuk (Kovalchuk, 2021), P. Kotler (Kotler, 2016), Y. Larina, Y. Marchuk, O. Zozulov, V. Parcak, Vol. 9 No.…”
Section: Research and Resultsmentioning
confidence: 99%
“…In doing so, brand values, brand goals or more general information that helps the employee in understanding the brand and his/her role in delivering the brand message can be part of the employee focussed brand knowledge dissemination. Previous research found a variety of desirable attitudinal outcomes, for example: brand identification (Ngo, Nguyen, Huynh, Gregory & Cuong, 2019), brand involvement (Biedenbach, Biedenbach, Hulté n & Tarnovskaya, 2022), organizational identification (Bravo et al, 2021), customer identification (Bravo et al, 2021), brand commitment (King & Grace, 2010). Moreover, direct positive effects on role clarity (King & Grace, 2010) have been found.…”
Section: Linking Brand Knowledge Dissemination and Corporate Brand Pridementioning
confidence: 98%
“…Keeping enough cash on hand to maintain ties, on the other hand, can make organizations more resilient in times of crisis. For an organization to survive, organizational resilience is essential for both everyday operations and times of crisis [ 16 ]. Resilience is the ability to continuously rebuild and absorb stress, which is something that organizations want to do faster than their competitors when reallocating resources [ 17 ].…”
Section: Literature Reviewmentioning
confidence: 99%